COVID-19 Vaccines and Public Anxiety: Antibody Tests May Be Widely Accepted - Liu, Leyuan; Wang, Xiaoxiao; Li, Xiaoguang; Li, Nan (Frontiers in Public Health, 2022)
Abstract: Background:More than 200 countries are experiencing the coronavirus disease (COVID-19) pandemic. COVID-19 vaccination strategies have been implemented worldwide, and repeat COVID-19 outbreaks have been seen. The purpose of this study was to investigate the impact of COVID-19 vaccination on the reduction of perceived anxiety and the association between public anxiety and antibody testing intention during the COVID-19 pandemic. Methods: Chinese adults aged 18 and over were surveyed using an anonymous online questionnaire in April and May 2021. The questionnaire collected sociodemographic characteristics, vaccination characteristics, perceived anxiety due to COVID-19, and attitudes toward future antibody testing after COVID-19 vaccination. Perceived anxiety was assessed on a visual analog scale (VAS). Multivariate logistic regression analysis was used to determine the factors influencing future antibody detection. Results: A total of 3,233 people were investigated, 3,209 valid questionnaires were collected, and the response rate was 99.3%. Of the 3,209 respondents, 2,047 were vaccinated, and 1,162 were unvaccinated. There was a significant difference in anxiety levels between vaccinated and unvaccinated respondents (24.9±25.4 vs. 50.0±33.1, respectively). With the local spread of COVID-19 in mainland China, the public anxiety VAS scores increased by 15.4±25.6 (SMD=120%) and 33.8±31.7 (SMD=49%) among vaccinated and unvaccinated respondents, respectively. Of the 2,047 respondents who were vaccinated, 1,626 (79.4%) thought they would accept antibody testing. Those who displayed more anxiety about acquiring COVID-19 disease were more likely to accept COVID-19 antibody testing. If the antibody test results showed protective antibodies, 1,190 (58.1%) were more likely to arrange travel plans in China, while 526 (25.7%) thought they would feel safer traveling abroad. Conclusion: COVID-19 vaccination strategies help reduce public anxiety. However, public anxiety may be elevated as the local transmission of COVID-19 occurs in mainland China, which is usually caused now by imported cases. Those who display more anxiety choose to have antibody testing. Improving the accessibility of COVID-19 antibody tests can help ease public anxiety and enhance the confidence of some people to participate in social activities. Keywords: COVID-19；SARS-CoV-2；vaccine；antibody tests